Role of neutrophil-to-lymphocyte ratio and platelet-to-lymphocyte ratio in diagnosing neonatal sepsis - Hasibuan, Beby S.; Dasatjipta, Guslihan; Lubis, Bugis M.; Sanny, Sanny (Narra J, 2024)
Clinical manifestations of neonatal sepsis are often unspecified. Therefore, sepsis biomarkers could be used to support diagnosis while waiting for blood culture results, such as the neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR). The aim of this study was to evaluate the role of NLR and PLR as diagnostic markers in neonatal sepsis. A cross-sectional study was conducted at Haji Adam Malik General Hospital, Medan, Indonesia, from April to October 2019. This study included neonates aged less than 28 days, diagnosed with suspected sepsis, and had no previous history of antibiotics administration. Patients underwent clinical assessment, laboratory examination, and blood culture. Patients were grouped into sepsis and non-sepsis based on the blood culture results. The median hematological examination and the range of NLR and PLR in both the sepsis and non-sepsis groups were subjected to analysis using the Mann-Whitney U test to assess differences. NLR and PLR optimal cut-off values were determined using a receiver operator curve (ROC) with a confidence interval of 95%. A total of 137 neonates were enrolled, of which 49 were classified as sepsis and 89 as non-sepsis based on blood culture results. The optimal cutoff values for NLR and PLR were 2.75 and 11.73. Using those cutoff values, NLR and PLR could predict neonatal sepsis with sensitivities of 52.1% and 47.9%, specificities of 50.6% and 47.2%, area under the curve (AUC) of 0.46 and 0.47, with p=0.525 and p=0.662, respectively. Further investigation is warranted to refine the NLR and PLR utility and enhance diagnostic accuracy in clinical practices.